LEVEL OF STUDENT SATISFACTION WITH PROJECT BASED LEARNING MODELS IN 2D CAD COURSES - Andrian Wisnu Dewangga; Andrian Riyadi; Fajrin Sidiq Muzaffarul Zaman (Journal of Automotive Technology Vocational Education, 2024)
This research aims to explore and analyze the level of student satisfaction with the application of the project-based learning (PBL) model in the 2D Computer-Aided Design (CAD) course. The research method used is a survey and data analysis involving students who take 2D CAD courses and are involved in project-based learning. This research includes collecting data from students through a questionnaire specifically designed to assess student perceptions of the PBL learning model, level of involvement in project activities, understanding of the material, and overall level of satisfaction. The data was then analyzed quantitatively to evaluate the level of student satisfaction with PBL in the 2D CAD course. The results of this research showed that the level of student satisfaction with project based learning in CAD courses reached a maximum average score of 68% in the satisfaction category, this states that students were satisfied with learning project based learning in 2D CAD courses. This research provides insight into the effectiveness of the Project Based Learning learning model in increasing student satisfaction in 2D CAD courses, which can be used to optimize teaching methods in the future. Keywords: Computer-Aided Design, Project-based learning, Student satisfaction